REGISTER CATEGORIES (FIELD, TENOR, MODE) OF THE TEXT - Darong, Hieronimus Canggung (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
This study is concerned with the employment of Systemic Functional Linguistics (SFL) theory in analyzing a speech text. The selected text was reconstructed into some clauses and sentences and subsequently was analyzed in terms of its field, tenor, and mode. The results of the analysis have shown that the register category of the field of the text is the action of America’s change. The tenor as the realization of the interpersonal meaning of the text was the establishment of an intimate relationship that enables the orator to gain support from the audience. Meanwhile, the mode of the texts is categorized as spoken mode because the texts make use of simple nominal groups. Further studies need to cope with other ways of examining field, tenor, and mode as proposed by SFL theory.